2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610860
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing classification accuracy of wrist movement by denoising sEMG signals

Abstract: This paper presents identification of 4 different wrist movements by analyzing fore-arm surface Electromyogram (sEMG) signals. In order to reduce noise picked up during the recording, wavelet based denoising is applied using Daubechies mother wavelet. Spectral features along with Wilson's amplitude were extracted and given to a linear classifier. The experimental result shows better recognition performance using the given features when denoising is applied. The maximum accuracy for identification of four wrist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…They reported better results using the db4 at level 3. These results appear to be consistent with the literature, since most studies have reported using either the db2 [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ] or the db4 [ 67 , 80 , 81 , 82 , 83 , 84 ]. In terms of the optimal decomposition level, level 4 appears to be the most widely used [ 5 , 19 , 71 , 77 , 82 , 85 , 86 ], while the level 3 is also frequently chosen [ 25 , 72 , 87 , 88 , 89 , 90 ].…”
Section: Contaminant Reduction Methodssupporting
confidence: 92%
“…They reported better results using the db4 at level 3. These results appear to be consistent with the literature, since most studies have reported using either the db2 [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ] or the db4 [ 67 , 80 , 81 , 82 , 83 , 84 ]. In terms of the optimal decomposition level, level 4 appears to be the most widely used [ 5 , 19 , 71 , 77 , 82 , 85 , 86 ], while the level 3 is also frequently chosen [ 25 , 72 , 87 , 88 , 89 , 90 ].…”
Section: Contaminant Reduction Methodssupporting
confidence: 92%
“…They reported better results using the db4 at level 3. These results appear to be consistent with the literature, since most studies have reported using either the db2 [73][74][75][76][77][78][79] or the db4 [67,[80][81][82][83][84]. In terms of optimal decomposition level, level 4 appears to be the most widely used [5,19,71,77,82,85,86], while the level 3 is also frequently chosen [25,72,[87][88][89][90].…”
Section: Denoising Methods After Wavelet Decompositionsupporting
confidence: 87%
“…The proposed method uses a cubical function that yields more reduction in the transformed amplitude near zero and no reduction at threshold λ The values above λ are not altered. The cubical thresholding method can be defined mathematically by 60 :…”
Section: Methodsmentioning
confidence: 99%